New application of Aspergillus versicolor in promoting plant growth after suppressing sterigmatocystin production via genome mining and engineering. Issue 1 (22nd November 2022) - Ma, Siqi; Zhao, Donglin; Han, Xiaobin; Peng, Yulong; Ren, Tingting; Wang, Mei; Wan, Jun; Ding, Jilin; Du, Xiuchun; Zhao, Fubin; Li, Yiqiang; Zhang, Chengsheng
Abstract: Aspergillus genus is a key component in fermentation and food processing. However, sterigmatocystin (STE)—a mycotoxin produced by several species of Aspergillus —limits the use of some Aspergillus species (such as Aspergillus versicolor, Aspergillus inflatus, and Aspergillus parasiticus ) because of its toxicity and carcinogenicity. Here, we engineered an STE‐free Aspergillus versicolor strain based on genome mining techniques. We sequenced and assembled the Aspergillus versicolor D5 genome (34.52 Mb), in which we identified 16 scaffolds and 54 biosynthetic gene clusters (BGCs). We silenced cytochrome P450 coding genes STC17 and STC27 by insertional inactivation. The production of STE in the Δstc17 mutant strain was increased by 282% but no STE was detected in the Δstc27 mutant. Metabolites of Δstc27 mutant exhibited growth‐promoting effect on plants. Our study makes significant progress in improving the application of some Aspergillus strains by restricting their production of toxic and carcinogenic compounds. Abstract : The genome of A. versicolor D5 is 34.52 Mb and consists of 54 biosynthetic gene clusters. Sterigmatocystin production can be suppressed by silencing the P450‐coding gene STC27. The sterigmatocystin‐free Δstc27 mutant strain has the activity of promoting plant growth, in contrast to the inhibiting effect of the wild strain D5.